2018
DOI: 10.1016/j.jotr.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction Internal Fixation versus External Fixation with Limited Internal Fixation for Displaced Comminuted Closed Pilon Fractures: A Randomised Prospective Study

Abstract: Background: Pilon fractures involve the dome of the distal tibial articular surface. The optimal treatment for high-energy pilon fractures remains controversial. Some authors advocate the use of open reduction and internal fixation (ORIF) to avoid articular incongruence. Others advocate the use of bridging external fixation with limited internal fixation (EFLIF) to reduce soft tissue complications. Literature reports of prospective studies comparing the radioclinical outcomes of ORIF and EFLIF in high-energy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…As for treatment with CEF, only a few studies have reported the treatment of tibial pilon fractures (especially for AO/OTA 43C3 type). In a comparative prospective study, Ahmed [ 8 ] compared 22 patients with ORIF and 20 with CEF. They reported no differences in the AOFAS score, arthritis, or pseudoarthrosis at the 2-year postoperative follow-up at a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…As for treatment with CEF, only a few studies have reported the treatment of tibial pilon fractures (especially for AO/OTA 43C3 type). In a comparative prospective study, Ahmed [ 8 ] compared 22 patients with ORIF and 20 with CEF. They reported no differences in the AOFAS score, arthritis, or pseudoarthrosis at the 2-year postoperative follow-up at a single institution.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the mean score continued to decline from 86.6 to 82.1 to 79.7, respectively. Imren et al, Rayan et al, Patra et al, and Sahin et al all reported one-year mean AOFAS scores of 86.6, 86.7, 76.3, and 80.4, respectively [ 30 , 31 , 33 ]. Kapoor et al reported a mean MMAS score of 79.8 from 16 patients [ 27 ].…”
Section: Reviewmentioning
confidence: 99%